2017
DOI: 10.9790/487x-1906065467
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents and Consequences of Employee Engagement: A Conceptual Study

Abstract: Employee engagement is a psychological state of mind of doing the work with full of energy, enthusiasm and dedication which can provide the competitive advantage of an organization. The purpose of this paper is to synthesize prior literature to identify antecedents and consequences of employee engagement. This literature review shows that prior studies examined diverse types of antecedences as well as consequences of employee engagement. Results of these existing studies are varied and inconclusive which leads… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 86 publications
1
21
0
Order By: Relevance
“…Employee engagement is generally recognized as the mutual interaction between employees and the organization [17]. Employee engagement is an important issue in the human resource department as it is very critical in achieving organizational success and competitiveness and engaged employees can contribute to organizational performance [18]. Engaged employees put more effort toward their work and are likely to go beyond their required and expected amount of work tasks [19].…”
Section: Research Questionmentioning
confidence: 99%
“…Employee engagement is generally recognized as the mutual interaction between employees and the organization [17]. Employee engagement is an important issue in the human resource department as it is very critical in achieving organizational success and competitiveness and engaged employees can contribute to organizational performance [18]. Engaged employees put more effort toward their work and are likely to go beyond their required and expected amount of work tasks [19].…”
Section: Research Questionmentioning
confidence: 99%
“…In order to revise the trend, the area of land equipped with irrigation facilities needs to be increased. (Aktar and Pangil, 2017) aptly noted that employment engagement is a psychological state of mind of doing the work with full of energy, enthusiasm and dedication which can only be sustained by the gains made or benefits derived. This calls for more investment in irrigation facilities in the continent to ensure sustainability of agriculture.…”
Section: Estimated Resultsmentioning
confidence: 99%
“…It is apparent that the feminine gender will benefit from such conducive and productive work environment in agriculture. For instance, Aktar and Pangil (2017) observed that Vincent-Höper et al (2012) noted that the relationship between work engagement and career satisfaction was stronger for women than men from a survey including 530 women and 602 men working in different occupations.…”
Section: Estimated Resultsmentioning
confidence: 99%
“…Although various studies have tried to understand what drives employees' engagement, the specialised literature on the employee engagement background does not represent much experimental research [38]. The present section expands on the contemporary logic and proof of employee engagement motivation [36] (figure 1). Saks [38] conducted a study to examine the antecedents of Engagement with a sample of 102 Canadian employees in different positions within various Canadian organizations who had been in their job for four years on average.…”
Section: Antecedents Of Engagementmentioning
confidence: 99%
“…The search for the antecedents of employee engagement is relatively new [36]. Researchers have identified that much of the employee engagement literature has come from practitioners and consultants, but considerable academic research has been achieved [37].…”
Section: Antecedents Of Engagementmentioning
confidence: 99%